CORHI-X: a Python tool to investigate heliospheric events through multiple observation angles and heliocentric distances - Cappello, Greta M.; Temmer, Manuela; Weiler, Eva; Liberatore, Alessandro; Möstl, Christian; Amerstorfer, Tanja (Frontiers in Astronomy and Space Sciences, 2025)
The CORonagraph and Heliospheric Imager data eXplorer (CORHI-X) is an open-source tool designed for the Heliophysics community to foster multi-spacecraft studies. CORHI-X enables users to easily visualize multi-spacecraft constellations, their overlapping fields of view (FoV), and the occurrence of coronal mass ejections (CMEs) over defined time intervals beginning in 2019. CORHI-X is accessible via a Python Streamlit interface, where users can select coronagraphs (e.g., STEREO-A/COR1-COR2, SOHO/C2-C3, SOLAR ORBITER/Metis) and heliospheric imagers (e.g., STEREO-A/HI-A, PARKER SOLAR PROBE/WISPR, SOLAR ORBITER/SoloHI). The tool not only provides spacecraft positions and FoVs of selected instruments, but also ensures that FoVs are plotted only when the corresponding spacecraft data are available. Indeed, the online archives of each instrument are checked monthly to retrieve observation dates, ensuring that CORHI-X automatically incorporates the latest data. For an effective search for eruptive events potentially appearing within the instrument’s FoVs, CORHI-X is linked to two different CME catalogs (DONKI and HI-Geo, respectively). The user can visualize specific CMEs and propagate them over distance to identify which events may have entered the FoV of one or more instruments. Users can also manually enter their own CME input parameters (propagation direction, speed, time, width, and longitude) via the interface. For propagation, a simple drag-based model is incorporated in the visualization of the spacecraft constellation.